2011
DOI: 10.1128/jvi.05045-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Clonal Lineage of HIV-1 Envelope V2/V3 Conformational Epitope-Specific Broadly Neutralizing Antibodies and Their Inferred Unmutated Common Ancestors

Abstract: V2/V3 conformational epitope antibodies that broadly neutralize HIV-1 (PG9 and PG16) have been recently described. Since an elicitation of previously known broadly neutralizing antibodies has proven elusive, the induction of antibodies with such specificity is an important goal for HIV-1 vaccine development. A critical question is which immunogens and vaccine formulations might be used to trigger and drive the development of memory B cell precursors with V2/V3 conformational epitope specificity. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
517
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(530 citation statements)
references
References 61 publications
12
517
1
Order By: Relevance
“…The difficulty in eliciting bnAbs has been attributed to the enormous antigenic diversity of the envelope glycoprotein and to the dense N-linked glycan coat that covers Env (the ‘glycan shield’). BnAbs isolated from chronic infection have a number of unusual features that have been selected to cope with the glycan shield including much longer than average HCDR3 loops 1012 . HCDR3s in most vertebrates have restricted lengths that predominantly encode loops of 12–16 amino acids upon VDJ recombination 9,1315 .…”
Section: Main Textmentioning
confidence: 99%
“…The difficulty in eliciting bnAbs has been attributed to the enormous antigenic diversity of the envelope glycoprotein and to the dense N-linked glycan coat that covers Env (the ‘glycan shield’). BnAbs isolated from chronic infection have a number of unusual features that have been selected to cope with the glycan shield including much longer than average HCDR3 loops 1012 . HCDR3s in most vertebrates have restricted lengths that predominantly encode loops of 12–16 amino acids upon VDJ recombination 9,1315 .…”
Section: Main Textmentioning
confidence: 99%
“…The V1V2-glycan bnAb class was the first of the new generation of bnAbs discovered (14, 15) (McCoy and Burton this volume). V1V2-glycan bnAbs, such as the PG9, CH01, PGT145 and CAP256-VRC26 lineages, are characterized by anionic, often tyrosine-sulfated, long and protruding CDR H3s that penetrate HIV envelope glycans and recognize a discontinuous epitope at the apex of the HIV-1 spike (14, 15,19,22,25,5154).…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…V1V2 bnAb interactions with various glycans and direct strand-strand contact between the extended CDR H3 and the C strand of the V1V2 domain are common traits among individual V1V2 bnAbs (51, 52, 55, 56). For immunogen design, despite V1V2 glycan bnAb preference for binding to a quaternary epitope, PG9, PG16 and CH01 bnAbs, as well as the CH01 lineage unmutated common ancestor (UCA), can also bind a minor subset of monomeric gp120 Envs (15, 57) and minimal Env forms (58). Crystal structures of the V1V2 glycan Env region in complex with V2 antibodies demonstrated that the V1V2 epitope can assume at least three conformations (52, 57): a β-strand, an α-helix and a 3 10 helix.…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations